1993
DOI: 10.1002/ar.1092350212
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic cell/lymphocyte clustering: Morphologic analysis by transmission electron microscopy and distribution of gold‐labeled MHC class II antigens by high‐resolution scanning electron microscopy

Abstract: Dendritic cells (DCs) are potent antigen-presenting cells for a variety of immune responses; however, their mechanism of action has not been established. It is known that DCs can cluster with one another and with other cell types during in vitro immune responses, and clustering may be essential for the activation of resting lymphocytes. In this study, ultrastructural examination of clusters that form during extended culture of enriched rat splenic DCs (approximately 70% DCs) is reported. DCs were readily disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…It is known that DCs accumulate at sites of infection or inflammation and can physically cluster with lymphocytes and with other DCs independent of MHC specificity [Inaba et al, 1984;Green and Jotte, 1985]. A striking feature of DCs is their constitutive expression of high levels of surface MHC class II antigens [Setum et al, 1993], which is confirmed in this study. In previous studies [Papaccio et al, 1994], it was demonstrated that infiltration occurring in NOD mice is a rather extensive and non specific process and which later undergoes a restriction.…”
Section: Discussionsupporting
confidence: 62%
“…It is known that DCs accumulate at sites of infection or inflammation and can physically cluster with lymphocytes and with other DCs independent of MHC specificity [Inaba et al, 1984;Green and Jotte, 1985]. A striking feature of DCs is their constitutive expression of high levels of surface MHC class II antigens [Setum et al, 1993], which is confirmed in this study. In previous studies [Papaccio et al, 1994], it was demonstrated that infiltration occurring in NOD mice is a rather extensive and non specific process and which later undergoes a restriction.…”
Section: Discussionsupporting
confidence: 62%
“…MHC II molecules have been reported to cluster with each other and with MHC class I (12,13); ''superdimers'' were even observed in the original three-dimensional crystal structure of human MHC II (14). A few reports documenting surface MHC II dimer of dimers have followed, (15)(16)(17) but neither the significance nor specificity of these interactions has been established nor has their formation in physiological settings been demonstrated.…”
Section: T He Initiation Of Adaptive Immunity Requires Presentation Omentioning
confidence: 99%
“…Under inverted phase contrast microscope of 40× object lens, monocytes isolated from PBMCs were observed to display as small round cells, and gradually stretch and adhere the plastic surface of the culture plate on day1(Figure 3(a)). On day8 after the stimulation of a cytokine cocktail for two days, mature DCs were exhibited as irregularly large round and suspension cells with blunt, elongate dendritic processes as previously reported (Figure 3(a)) [27, 28]. Furthermore, the phenotype of mature DCs was analyzed by FACS testing the expression of co-stimulatory molecules and maturation markers.…”
Section: Resultsmentioning
confidence: 77%